The Role of Madrasah Ibtidaiyah Teachers in Developing Students' Character in the Digital Era - Liawati Liawati (CV. Intake Pustaka, 2025)
This study explores the pivotal role of Madrasah Ibtidaiyah (MI) teachers in fostering students' character development amidst the challenges and opportunities presented by the digital era. Employing a qualitative library research approach, this research synthesizes findings from recent studies and theoretical frameworks to analyze the integration of character education within digital learning environments in MI settings. The findings indicate that MI teachers significantly influence character development by integrating Islamic values into digital learning platforms, utilizing differentiated learning strategies, and promoting digital literacy. These approaches have led to enhanced student discipline, responsibility, and empathy. The study underscores the necessity for MI teachers to receive continuous professional development in digital competencies and character education methodologies. Educational policies should support the integration of technology in character education to align with the demands of the digital era